REFORMASI ETIKA PROFESI SUSAN CRAWFORD SULLIVAN DAN IMAN YANG HIDUP - Agus, Guruh David (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
Faith is one of the objects of study in Living Religion studies that highlight religious beliefs experienced in the everyday lives of individuals in society. This research applies content analysis and uses two objects: various articles on the relationship between religion, welfare, and work ethic as material objects, and Susan Crawford Sullivan’s theory in Chapter Three of the book Living Faith: everyday religion and mothers in poverty (2011) as the formal object. Sullivan’s theory is used as a lens to examine several articles. The sentence in the final paragraph, “poor working mothers, mothers caring for their children, or single mothers – will connect with Congregations, labor unions, political organizations, or communities that can help them fight fo better opportunities and work environments” summarizes Sullivan’s theory on the reform of professional ethics. Living faith in professional societies should live in the nation’s work ethic, the work of the Church and religious communities, the purgatorial code of ethics for welfare stakeholders, the morality of religious elites and commoners, and within the mothers who are occupied and vocationally dedicated to adequately prospering “now” in this world.